STATUS SOSIAL EKONOMI DAN INTENSITAS KOMUNIKASI KELUARGA PADA IBU RUMAH TANGGA DI PANGGUNG KIDUL SEMARANG UTARA - Indrawati, Endang Sri (Jurnal Psikologi, 2015)
The aim of the study was to determine the correlation between socio-economic status and intensity of family communication of housewives in RW 02 Kelurahan Panggung Kidul, Sub-district of North Semarang. Subjects involved in the research were 73 subjects which were chosen based on proportionate stratified random sampling method. The data collection was conducted by using questionnaire to discover economic status and 37-item Intensity of Family Communication Scale (Î± = .886). Simple regression analysis result shows that socio- economic status is positively correlated to family communication intensity by housewives (r = .327; p = .005) with positive contribution 10.7%. It means that there is a positive correlation between socio-economic status with the intensity of family communication, socioeconomic status contribute 10.7% of the intensity of family communication.